HIV viral kinetics and T cell dynamics in antiretroviral naïve persons starting an integrase strand transfer inhibitor and protease inhibitor regimen. Issue 2 (4th March 2017) - Karris, Maile Y.; Jain, Sonia; Day, Tyler R.C.; Pérez-Santiago, Josué; Goicoechea, Miguel; Dubé, Michael P.; Sun, Xiaoying; Spina, Celsa; Daar, Eric S.; Haubrich, Richard H.; Morris, Sheldon; ,
Abstract : Background : Nucleos(t)ide reverse transcriptase inhibitor (NRTI)-sparing regimens may potentially minimize antiretroviral (ART) toxicities, but demonstrate mixed efficacy and toxicity results. The impact of an integrase strand transfer inhibitor (INSTI) and protease inhibitor (PI) regimen on HIV viral dynamics and T cell kinetics remains underdescribed. Objective : To compare the effect of raltegravir + ritonavir boosted lopinavir (RAL + LPV/r) to efavirenz/tenofovir disoproxil fumarate/emtricitabine (EFV/TDF/FTC) on HIV kinetics and T cell dynamics. Methods : Fifty participants naïve to ART underwent HIV viral kinetic sampling evaluated using biexponential mixed effects modeling. A subset of 28 subjects (with complete viral suppression) underwent flow cytometry and evaluation of soluble markers of inflammation at weeks 0, 4, and 48 of ART. Results : RAL + LPV/r compared to EFV/TDF/FTC resulted in a prolonged first phase viral decay rate (18 vs. 13 days p < 0.01). From weeks 0 to 4, RAL + LPV/r was associated with a trend toward greater decreases in activated CD4 + T cells (−3.81 vs. −1.18 p = 0.09) and less decreases in activated effector memory CD4 + T cells (−0.63 vs. −2.69 p -0.07). These trends did not persist to week 48. No differences were noted at any time point for soluble markers of immune activation. Conclusions : The prolonged first phase viral decay observed with RAL + LPV/r in persons starting ART did not result in differences in viral suppression at week 48. We also observed trends in declines in certain cellular markers of immune activation but it remains unclear if this could translate to long-term immunologic benefits in persons on an INSTI + PI.